Everybody's Family Romance : Reading Incest in Neoliberal America - Harkins, Gillian (Book collections on Project MUSE., 2009)
"In the 1990s, a boom in autobiographical novels and memoirs about incest emerged, making incest one of the hottest topics to connect daytime TV talk shows, the self-help industry, and the literary publishing circuit. In Everybody's Family Romance, Gillian Harkins places this proliferation of incest literature at the center of transformations in the political and economic climate of the late twentieth century. Harkins's interdisciplinary approach reveals how women's narratives about incest were co-opted by--and yet retained resistant strains against--the cultural logics of the neoliberal state. Across chapters examining legal cases on recovered memory, popular journalism, and novels and memoirs by Dorothy Allison, Carolivia Herron, Kathryn Harrison, and Sapphire, Harkins demonstrates that incest narratives look backward into the past. In these accounts, images of incest forge links between U.S. chattel slavery and the distributive impasses of the welfare state and between decades-distant childhoods and emergent memories of the present. In contrast to recent claims that incest narratives eclipse broader frameworks of political and economic power, Harkins argues that their emergence exposes changing structural relations between the family and the nation and, in doing so, transforms the analyses of American familial sexual violence"--Provided by publisher.